Jane Eyre and Wide Sargasso Sea’s Treatment of Feminism and its Reflection in Character Analysis - Rakhimova Ugiloy Akbarovna (Indonesian Journal of Innovation Studies, 2022)
“Jane Eyre” and “Wide Sargasso Sea” are regarded as the masterpieces that vividly express the elements of feminism. Before analyzing and proving this idea,it is necessary to determine and define the concept of feminism.One of the best works was Charlotte Bronte’s “Jane Eyre”. At that time, for Jane, as a member of the lowest class, she is always looked down upon by those potentates with money and power. For people like her, they have no dignity; the rich can treat them at random and need not bother to give them any esteem. But Jane Eyre never surrenders to those snobbish people who despise the poor and the weak parochially and ruthlessly. In her whole life, she plunges herself into struggling for esteem which in her mind is deserved by any human being rather than a privilege for the wealthy people.